DAMPAK PERSEPSI KORUPSI PAJAK DAN KONFLIK WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DIMODERASI OLEH SOSIALISASI DIREKTORAT JENDRAL PAJAK - Tambun, Sihar; Septriani, Mila (Universitas 17 Agustus 1945 Jakarta, 2018)
AbstractThis study aims to determine the Impact of Tax Corruption and Against Perception (case study on individual taxpayers who work in North Jakarta). In this study using 4 variables, namely, variable perceptions of tax corruption (X1), taxpayer conflict (X2), taxpayer compliance (Y), socialization of the directorate general of taxes (Z).The sampling method of this study wa convenience sampling method. The population in this study were taxpayers who had worked especially in northern Jakarta, and the samples taken were 100 respondents. Where the perception of tax corruption, socialization of the directorate general of tax has a significant effect on taxpayer compliance. Tax conflicts do not have a significant effect on taxpayer compliance. Keywords: Perception of tax corruption, taxpayer conflict, taxpayer compliance, socialization of director general of tax.